Electric Parameter Extractions Using a Broadband Technique from Coaxial Line Discontinuities (International Journal of Scientific Research and Management (IJSRM), 2019)
We have proposed a simple technique for extracting high frequency material complex relative permittivity from 0.1 GHz up to beyond 5.1 GHz despite the test fixture’s discontinuities along with the characteristic impedance. The frequency range limitation depends on the test fixture’s sizes. Based on the S-parameter measurements, the overall technique associates the test fixture in which the sample to characterize is inserted and the technique for altering the propagation constant of the considered region. Mathematics concepts, through their formulations, allow extracting material complex relative permittivity. The technique foundation is primarily based on the fixture calibration when there is a filling up of vacuum. A coaxial test cell is used to validate the extraction procedure. That fixture is suitable for measuring material electric parameters used in medical and civil engineering, telecommunications, and oil and gas domains. We have presented results ensuing from measures of spring water and biological materials: human tissue and liquid 900 MHz. Both biological materials are liquids and react as a muscle subjected to an electromagnetic wave. The technique is broadband, making it easy to fill up the test cell with the sample to be tested.